2021
DOI: 10.1037/edu0000626
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in early literacy: Boys’ response to formal instruction.

Abstract: Research consistently documents that girls outperform boys in literacy achievement, yet, when considering the starting point-early literacy-we do not have consensus on the origin, meaningful nature, or persistence of such differences. In this two-part study analyzing 5,816 Norwegian students (48.1% girls, average age of 6.1 years), we first considered the presence and meaningful nature of gender differences at school entry. Presence of differences, advantaging girls, was found in letter-recognition, phonemic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
19
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 58 publications
6
19
0
3
Order By: Relevance
“…Sigmundsson et al (2017) fant at barn i gjennomsnitt kunne navngi faerre enn halvparten av både store og små bokstaver i det norske alfabetet ved skolestart. McTigue et al (2020) fant at de fleste elevene kunne kjenne igjen store bokstaver, men at svaert få elever var lesere ved skolestart. I begge studiene var det stor variasjon i elevene sine språkferdigheter.…”
Section: Bokstavkunnskapens Betydningunclassified
See 2 more Smart Citations
“…Sigmundsson et al (2017) fant at barn i gjennomsnitt kunne navngi faerre enn halvparten av både store og små bokstaver i det norske alfabetet ved skolestart. McTigue et al (2020) fant at de fleste elevene kunne kjenne igjen store bokstaver, men at svaert få elever var lesere ved skolestart. I begge studiene var det stor variasjon i elevene sine språkferdigheter.…”
Section: Bokstavkunnskapens Betydningunclassified
“…Man ser at forskjellene i bokstavgjenkalling er store blant elevene i vår studie. McTigue et al (2020) finner at de fleste elevene kan kjenne igjen store bokstaver, noe som ikke helt samsvarer med vår studie. Imidlertid finner McTigue et al (2020) at det er stor variasjon i elevene sine ferdigheter når det gjelder bokstavgjenkalling, noe som samsvarer med vår studie.…”
Section: Fremlydsanalyse Og Bokstavgjenkallingunclassified
See 1 more Smart Citation
“…Recent research reports a larger Scan Path Length and Saccade Amplitude in female subjects [ 30 ]. Also, in tests of early reading ability Harper and Pelletier [ 31 ] found no gender differences in children’s performance. However, the study employing eye-tracing methodology revealed gender differences in reading abilities indicated by Saccade Duration, Regression Rate, and Blink Rate [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Students' "performance on reading literacy tasks upon entering primary school" and "years of attending preschool" did not have significant effects on the item wording effects. This result may be due to the students' grade level, as longitudinal studies (e.g., McTigue et al, 2020;Roth, Speece, & Cooper, 2002) indicate that performance differences in early literacy may diminish or the strength of the relationship between achievement and early literacy may decline over the years, due to other sources for variation (e.g., teachers, education quality, and school). This result can additionally be supported by evidence indicating that younger respondents tend to have more problems interpreting the negative expression of a statement (Marsh, 1996;Michaelides, 2019;Weems et al, 2003Weems et al, , 2006.…”
mentioning
confidence: 99%